When High-Powered People Fail - Beilock, Sian L.; Carr, Thomas H. (Psychological Science, 2005)
We examined the relation between pressure-induced performance decrements, or “choking under pressure,” in mathematical problem solving and individual differences in working memory capacity. In cognitively based academic skills such as math, pressure is thought to harm performance by reducing the working memory capacity available for skill execution. Results demonstrated that only individuals high in working memory capacity were harmed by performance pressure, and, furthermore, these skill decrements were limited to math problems with the highest demands on working memory capacity. These findings suggest that performance pressure harms individuals most qualified to succeed by consuming the working memory capacity that they rely on for their superior performance.